2013
DOI: 10.5198/jtlu.v6i2.308
|View full text |Cite
|
Sign up to set email alerts
|

Explaining walking distance to public transport: The dominance of public transport supply

Abstract: Potential influences on explaining walking distance from home to access public transport are investigated, including trip and demographic characteristics and public transport supply. In Sydney, Australia, people walk farther to the train than to the bus, the distributions of walking distances are different for each mode, and the trip and demographic characteristics of train and bus users are different. Given the decision to walk to public transport, demographic characteristics such as age, gender, income, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(204 citation statements)
references
References 19 publications
5
192
1
6
Order By: Relevance
“…In low-income adult populations, walking large distances is associated with a low-quality of life, 33,34 to date there is no evidence that walking extremely large distances is associated with lower quality of life or enjoyment in children. In the United States it is reasonable to expect that elementary school students walk up to 1.35 miles per 30-min period to get to school.…”
Section: Discussionmentioning
confidence: 99%
“…In low-income adult populations, walking large distances is associated with a low-quality of life, 33,34 to date there is no evidence that walking extremely large distances is associated with lower quality of life or enjoyment in children. In the United States it is reasonable to expect that elementary school students walk up to 1.35 miles per 30-min period to get to school.…”
Section: Discussionmentioning
confidence: 99%
“…Using the proposed weighted measures, we obtained similar results, but the alternatives with more LRT lines scored lower in coverage. This is explained by the differentiated passenger behavior: according to the literature, passengers are willing to walk longer distances to a faster mode [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that actual walk catchment area depends on the mode and level of service (such as wait time) and that the 85 percentile was more than 500 m for bus and 1200 m for rail. Daniels and Mulley [4] showed that in Sydney, Australia, the walk distance to station mostly depends on the mode and that people walk further for a faster mode. Similarly, the station walk coverage The coverage area accessible by the metro network, measured as 500 m from each station divided by the area serviced (A)…”
Section: Methodsologymentioning
confidence: 99%
“…To account for characteristics that may influence PA, 33 we assessed individual variables, including sex, age, marital status, education, monthly household income, neighborhood SES, occupation over the last 30 days, years of residency in the neighborhood, and motorcycle and car ownership, as potential confounders. The study also evaluated the modes of transportation and minutes spent on each mode (public bus, TM, feeder bus, car, taxi, motorcycle, and others) over the previous 7 days.…”
Section: Individual Covariatesmentioning
confidence: 99%